Challenges to democracy in Argentina.Thirty years later - del Barco, Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This is an analysis of democracy in Argentina, in its first thirty years. However, this democracy must face some challenges, such as: strengthen democracy, building of the Republic, overcoming the wrath of control, defeating the law of hate, rebuilding the culture of work, return to policy the sense of service.